Development of the laser isotope separation method to study for the neutrino-less double beta decay of 48Ca. Issue 1 (1st January 2022) - Ogawa, I; Kawashima, Y; Hiraiwa, T; Tozawa, M; Niki, H; Tokita, S; Han, B; Okuda, H; Miyanaga, N; Umehara, S; Matsuoka, K; Yoshida, S
Abstract: Search for the ultra-rare process, neutrino-less double beta decay, is a powerful tool to test the Majorana nature of neutrinos. Among the potential double beta decay nuclei, 48 Ca has the largest Q-value, hence we can expect the measurement with least background. On the other hand, due to its low natural abundance, isotope enrichment is essential to achieve the sensitivity in the region of interest (inverted/normal mass hierarchy of neutrinos). We have been developing a laser isotope separation method using a tunable semiconductor laser that can excite only a specific isotope ( 48 Ca). The laser is irradiated perpendicular to the collimated calcium vapor beam. Only 48 Ca atoms are separated by deflecting them from the original atomic beam by momentum transfer due to multiple absorption and emission of laser photons. The isotope separation is confirmed by irradiating an ionization laser and time-of-flight measurement. Following the success of the proof-of-principle experiment, we are now developing the mass production system which include efficient generation of atomic beams, frequency-stabilized high-power laser, efficient laser irradiation method, and collection method of deflected isotope beams. In this paper, we report on the status and prospects of these developments.